Preliminary assessment of offshore wind speed around Cyprus based on Sentinel-1 Level 2 OCN data - Hadjipetrou, Stylianos; Liodakis, Stelios; Sykioti, Anastasia; Fayad, Philip; Akylas, Evangelos; Park, No-Wook; Kyriakidis, Phaedon (My University, 2020)
Detailed resource or impact assessment studies often call for higher spatial resolution data products. Remote sensing data e.g., SAR (Synthetic Aperture Radar) provide high spatial resolution wind information but suffer from the satellite’s relatively poor revisit time. This paper focuses on the preliminary assessment of offshore wind speed derived from diverse data sources, characterized by different spatial and temporal resolution. A univariate statistical analysis and a match-up comparison between in-situ Cyprus meteorological stations wind speed measurements and Sentinel-1A and 1B VV-polarized SAR wind field estimates were conducted for a two-year period between 1st June, 2017-1st June, 2019. Results indicate that SAR data overestimate the in-situ measurements resulting in an average bias of 0.7 m/s, which was gradually increasing in parallel to the wind speed values. Errors also proved to vary spatially with Akrotiri demonstrating the highest average errors comparing to Pafos and Larnaca. Despite the discrepancies found, Sentinel-1 SAR Level-2 OCN can be considered as a reliable source for offshore wind field estimation. The initial assessment presented in this paper can be considered as the basis for a future in-depth analysis of Cyprus offshore wind resource assessment.
Keywords: Bivariate Statistics; Sentinel-1; Validation; Weather monitoring stations